Acceptance of a COVID-19 vaccine and associated factors among pregnant women in China: a multi-center cross-sectional study based on health belief model - Tao, Liyuan; Wang, Ruitong; Han, Na; Liu, Jihong; Yuan, Chuanxiang; Deng, Lixia; Han, Chunhua; Sun, Fenglan; Liu, Min; Liu, Jue (Human vaccines & immunotherapeutics, 2021)
Background: Vaccine hesitancy has been recognized as an urgent public health issue. We aimed to explore the acceptance of a COVID-19 vaccine and related factors among pregnant women, a vulnerable population for vaccine-preventable diseases. Methods: A multi-center cross-sectional study among pregnant women was conducted in five provinces of mainland China from November 13 to 27, 2020. We collected sociodemographic characteristics, attitude, knowledge, and health beliefs on COVID-19 vaccination. Locally weighted scatterplot smoothing regression analysis was used to assess the trends of vaccination acceptance. Multivariable logistic regression was performed to identify factors related to vaccination acceptance. Results: Among the 1392 pregnant women, the acceptance rate of a COVID-19 vaccine were 77.4% (95%CI 75.1-79.5%). In the multivariable regression model, the acceptance rate was associated with young age (aOR = 1.87, 95% CI: 1.20-2.93), western region (aOR = 2.73, 95% CI: 1.72-4.32), low level of education (aOR = 2.49, 95% CI: 1.13-5.51), late pregnancy (aOR = 1.49, 95% CI: 1.03-2.16), high knowledge score on COVID-19 (aOR = 1.05, 95% CI: 1.01-1.10), high level of perceived susceptibility (aOR = 2.18, 95% CI: 1.36-3.49), low level of perceived barriers (aOR = 4.76, 95% CI: 2.23-10.18), high level of perceived benefit (aOR = 2.18, 95% CI: 1.36-3.49), and high level of perceived cues to action (aOR = 15.70, 95% CI: 8.28-29.80). Conclusions: About one quarters of pregnant women have vaccine hesitancy. Our findings highlight that targeted and multipronged efforts are needed to build vaccine literacy and confidence to increase the acceptance of a COVID-19 vaccine during the COVID-19 pandemic, especially for vulnerable populations.